TOLERANCE OF WINTER CROPS TO RESIDUAL HERBICIDES - NUNES, Anderson Luis; VIDAL, Ribas Antônio; GOULART, Ives Clayton Gomes dos Reis; KALSING, Augusto (Scientia Agraria, 2007)
Some crops, as the species cultivated in the winter, have few options of registered selective herbicides. Due to the lack of information, some farmers use products in an inadequate form, that could cause undesirable consequences. The present work evaluated the tolerance of winter crops to residual herbicides. For this, an experiment was made between June and August of 2005, in the greenhouse of the College of Agronomy of the Universidade Federal do Rio Grande do Sul (UFRGS), located in Porto Alegre county. The experimental design used was the completely randomized, using the bifactorial arrangement, with five repetitions. The factor A consisted of the crops: Avena sativa L. (wild oat), Hordeum vulgare L. (barley), Raphanus sativus var. oleiferus Metzger. (oil seed radish) and Triticum aestivum L. (wheat) and factor B consisted of the preemergence herbicides application: atrazine (3,0 kg ha-1), cloransulam (0,04 kg ha-1), imazaquin (0,14 kg ha-1), metribuzin (0,144 kg ha-1), S-metolachlor (1,92 kg ha-1) and control. Oil seed radish and wheat crops had not presented tolerance to the used products. Plants of wild oat had been tolerant to cloransulam and barley presented tolerance to the herbicidas atrazine and cloransulam.